Evaluation of Imidacloprid Induced Changes in Thyroid Gland and its Amelioration with Withania somnifera in Wistar Rats - Samala, Soujanya; Mekala, Lakshman; Doppalapudi , Madhuri; Alla, Gopala Reddy; Rao, Rama (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
The study was conducted on a total of 48 female Wistar rats divided into four groups, each containing 12 rats. Group 1 was control, group  2 was imidacloprid control, group 3 was Withania somnifera control and group 4 was administered with both imidacloprid and Withania  somnifera. The rats of group 3 and 4 were subjected to oral treatment of Withania somnifera (1 gm/kg feed) for a period of 30 days to  measure the protective effect against thyroid toxicity induced by imidacloprid (30 mg/kg body weight/day for 30 days). Hormonal assays  showed a significant (p
Keywords: Electron microscopy; Imidacloprid; Rats; Thyroid gland; Withania somnifera